High field electroformation of sodium bismuth titanate and its solid solutions with barium titanate. Issue 9 (16th February 2021) - Ren, Pengrong; Gehringer, Maximilian; Huang, Binxiang; Hoang, An-Phuc; Steiner, Sebastian; Klein, Andreas; Frömling, Till
Abstract : High electrical fields induce an acceptor doping dependent electroformation process to a highly conductive state in Na1/2 Bi1/2 TiO3 . The mechanism involves mobile sodium and oxygen vacancies. Abstract : Lead-free ceramics based on Na1/2 Bi1/2 TiO3 (NBT) have been shown to exhibit excellent ferroelectric properties putting them amongst the best materials to replace lead-based piezoelectrics. The defect chemistry of NBT is, however, very complex. High oxygen ionic conductivity can be induced by acceptor doping or bismuth evaporation, which is quite detrimental to the ferroelectric properties. Nevertheless, this conductivity is non-linearly dependent on the acceptor concentration, which allows for tuning of NBT-based material from highly ionically conducting to highly resistive. This unique behavior raises the question of whether NBT ceramics also need to be treated differently with respect to high electric fields as they are used for ferroelectric and dielectric applications. High field electrodegradation experiments have been performed on NBT and a solid solution with BaTiO3 (BT) to elucidate this. It could be shown that reversible electroformation can be induced, which is non-linearly dependent on acceptor concentration. Additionally, a fast surface degradation process could be identified, which could be attributed to a reversible field-induced change in composition at the anode due to sodium becoming mobile. These results will be of high importance for reliability investigations of NBT based material and also hint towards possible applications in resistive switching memory applications.